Treatment of an Erratic Extraction Socket for Implant Therapy in a Patient with Chronic Periodontitis - Yusuke Hamada; Srividya Prabhu; Vanchit John (Hindawi Limited, 2016)
As implant therapy becomes more commonplace in daily practice, preservation and preparation of edentulous sites are key. Many times, however, implant therapy may not be considered at the time of tooth extraction and additional measures are not taken to conserve the edentulous site. While the healing process in extraction sockets has been well investigated and bone fill can be expected, there are cases where even when clinicians perform thorough debridement of the sockets, connective tissue infiltration into the socket can occur. This phenomenon, known as "erratic healing," may be associated with factors that lead to peri-implant disease and should be appropriately managed and treated prior to surgical implant placement. This case report describes the successful management of an erratic healing extraction socket in a 62-year-old Caucasian male patient with chronic periodontitis and the outcomes of an evidence-based treatment protocol performed prior to implant therapy. Careful preoperative analysis and cone beam computed tomography imaging can help detect signs of impaired healing in future implant sites and prevent surgical complications.